Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1097/00000542-199501000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Sevoflurane in Children 

Abstract: Sevoflurane with nitrous oxide provides satisfactory anesthetic induction and intubating conditions; however, induction using sevoflurane without nitrous oxide is associated with a high incidence of patient excitement and prolonged time to intubation. There were greater decreases in heart rate and systolic blood pressure during induction with halothane than with sevoflurane; however, these differences may be dose-related. The more rapid emergence with sevoflurane when compared with halothane is consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
130
2
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(148 citation statements)
references
References 32 publications
7
130
2
9
Order By: Relevance
“…Among the paediatric patients not receiving intraoperative analgesics, those maintained with sevoflurane required postoperative analgesics earlier than those who received halothane. The earlier time for extubation, requirement of analgesics and discharge readiness suggest that sevoflurane provided more rapid emergence and earlier awakening than halothane [4]. In a separate study sevoflurane was compared with propofol for induction and maintenance of anaesthesia [5].…”
Section: Discussionmentioning
confidence: 99%
“…Among the paediatric patients not receiving intraoperative analgesics, those maintained with sevoflurane required postoperative analgesics earlier than those who received halothane. The earlier time for extubation, requirement of analgesics and discharge readiness suggest that sevoflurane provided more rapid emergence and earlier awakening than halothane [4]. In a separate study sevoflurane was compared with propofol for induction and maintenance of anaesthesia [5].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we adopted 2.5% halothane as the inspired concentration (2 MAC EI ) for the halothane group in this study. The haemodynamic responses to > 1 MAC sevoflurane in infants and children have not been quantified, although blood pressure and heart rate responses during inhalational induction with inspired concentrations up to 7% sevoflurane have been unremarkable [20,21]. While a vaporiser delivering 7% sevoflurane is widely used, high concentrations (> 5%) of sevoflurane were reported to possibly induce electroencephalographic evidence of seizure activity [12].…”
Section: Figurementioning
confidence: 99%
“…The elevation of the ETsev concentration in a shorter time with the addition of nitrous oxide gave us the impression that indirectly, the anesthetic concentration in the brain had also risen more rapidly. Also, Sarner et al (11), in their study, determined that the duration for the ETsev to reach a concentration of 2% was reduced significantly in the N 2 O-added group.…”
Section: Discussionmentioning
confidence: 90%
“…Those who defend that it shortens the induction period have suggested that N 2 O accomplishes this by the second gas effect and the previously shown additive effects (11,18,19,30). The opponent group has advocated in their studies that N 2 O does not shorten the induction period and the addition of N 2 O during induction is unnecessary (9,10,22).…”
Section: Discussionmentioning
confidence: 98%